2018
DOI: 10.1177/2325967118768086
|View full text |Cite
|
Sign up to set email alerts
|

Radial Tears of the Lateral Meniscus—Two Novel Repair Techniques: A Biomechanical Study

Abstract: Background:A common treatment for radial tears of the meniscus has historically been partial meniscectomy. Owing to the poor outcomes associated with partial meniscectomy, repair of the meniscus is an important treatment option. It is important to evaluate different repair techniques for radial tears of the meniscus.Purpose/Hypothesis:The purpose of this study was to evaluate 2 novel techniques to repair radial tears of the lateral meniscus. The 2 techniques were compared biomechanically with the cross-suture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 32 publications
0
39
2
Order By: Relevance
“…13,[16][17][18] Many studies describe methods to repair radial tears of the midbody of the meniscus and posterior root tears. 2,[4][5][6][7]10,11 However, the literature lacks methods to repair a radial tear neighboring a posterior root. In past surgical studies, these radial tears were solely treated with a PM, which caused the development of medial compartment arthritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,[16][17][18] Many studies describe methods to repair radial tears of the midbody of the meniscus and posterior root tears. 2,[4][5][6][7]10,11 However, the literature lacks methods to repair a radial tear neighboring a posterior root. In past surgical studies, these radial tears were solely treated with a PM, which caused the development of medial compartment arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Radial tears along the meniscus mid-body can be treated with a partial meniscectomy (PM) or repaired using methods like the inside-out repair, the outside-in repair, and the all-inside repair. 2,3,[5][6][7][8] However, these repairs only alleviate symptoms to varying degrees 3,4 and are unable to restore the meniscus to its original function. 4 Root tears are surgically treated with a PM or reattached to the tibial plateau with a transtibial pull-out repair (TTPR) or suture anchor technique.…”
mentioning
confidence: 99%
“…In clinical practice, some oblique or cross-suture methods have been applied in the treatment of radial tears of the meniscus and have achieved good results [33][34][35]. Biomechanical studies have shown [36] that oblique sutures have the dual advantage of vertical sutures (superior biomechanical strength) and horizontal sutures (ease of application, longer sutures with a tendency to cover a larger meniscal tissue area).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, some oblique or cross-suture methods have been applied in the treatment of radial tears of the meniscus and have achieved good results [30][31][32] . Biomechanical studies have shown [33] that oblique sutures have the dual advantage of vertical sutures (superior biomechanical strength) and horizontal sutures (ease of application, longer sutures with a tendency to cover a larger meniscal tissue area).…”
Section: Discussionmentioning
confidence: 99%